Enhancing Early Childhood Creativity Through Loose Parts Play Activities Based on Islamic Values - S Septriany; A. Ahmadi (Manunggal Halim Jaya, 2026)
This study aims to improve early childhood creativity through loose parts play activities based on Islamic values at KB Wijaya Kusuma Pacitan. The research used a quantitative approach with a pre-experimental one-group pretest-posttest design involving 10 children. Data were collected through observation using a creativity assessment sheet covering fluency, flexibility, originality, and elaboration. The results showed a significant increase from a pretest mean of 6.8 to a posttest mean of 12.9. The paired sample t-test result (0.000 < 0.05) indicated a significant effect. Thus, loose parts play based on Islamic values is effective in enhancing early childhood creativity holistically.